PEMBARUAN METODE PEMBELAJARAN KITAB KUNING DI PONDOK PESANTREN SIDOGIRI PASURUAN - Erlin Indaya Ningsih (Prodi PAI Fakultas Tarbiyah IAI Miftahul Ulum, 2021)
In the context of islamic boarding school education, learning islamic classic book is a medium to distribute and examine islamic scholars’ books conducted by islamic boarding school as a way to teach islamic boarding school students as the next generation in the future, both of thought or morality. Ironically, learning islamic classic book often finds problems because the tradition of islamic classic book learning is only using oral dan writtten method. In addition, the method is unstructured and unsystematic, Al- Miftah Lil Ulum is a reform as a way to keep the authorizing of islamic classic book tradition as the characteristic of islamic boarding school. The research about reform of islamic classic book method is located in Sidogiri islamic boarding school, Pasuruan, where this is one of traditional islamic boarding schools doing islamic classic learning for children.